A Proposal for the Standardized Reporting of Error and Paradata Regarding Structure from Motion (SfM) 3D Models Used in Recording and Consolidating Archaeological Architecture. Issue 4 (November 2020) - Borrero, Mario; Stroth, Luke R.
Abstract: In the past decade, archaeologists have increasingly made use of photogrammetry, the process of creating 3D models from photographs, in a variety of field and lab settings. We argue that we must, as a discipline, develop a consistent methodology to ensure that 3D models are held to a consistent standard, including not only photographic protocol but also the documentation of model accuracy using an agreed-upon measure. To help develop this discussion, we present our system for incorporating photogrammetry into the documentation of architecture. This technique was developed at the site of Nim Li Punit, Belize, in 2018. Excavating architecture involves documenting the pre-excavated building, liberating overburden, documenting all in situ construction (including wall fall, fill stones, and standing architecture), drawing consolidated architecture, and documenting the final state of the post-excavated buildings. The generation of 3D models greatly assisted in all facets of the excavation, documentation, analysis, and consolidation processes. To ensure that our models were accurate, we documented the reprojection error and final model horizontal distortion to assess the quality of the model. We suggest that documenting both forms of error should become standard practice in any discussion of archaeological applications of photogrammetry.